Engaging in reflective practice via vlogs: Experience of Malaysian ESL pre-service teachers - Ong, Wei Ann; Swanto, Suyansah; Alsaqqaf, Asmaa (Indonesian Journal of Applied Linguistics, 2020)
Reflective practice serves as a vital area of teacher education and the impetus for professional development among pre-service teachers. Past research has lamented the lack of critical thought of the reflection made by pre-service teachers during their teaching practice. This paper presents a qualitative investigation into the use of video blogs (vlogs), which are mediated online. The participants of the study comprised 13 pre-service ESL teachers studying in an Institute of Teacher Education. The data for this study was gathered via the analysis of the vlogs and the focus group interview. Results indicate that the respondents expressed mixed reactions to the approach, where some have enjoyed the experience while some feared of being judged and feeling awkward seeing themselves in vlogs. Most respondents have centered their reflections on issues they encountered during lessons, but one has shown the ability to reflect on issues beyond the classroom setting. The outcome of the study implied the need for pre-service teachers to be given additional coaching on the ‘how’ aspect of reflection. In addition, there is a need to address technical issues faced by respondents in using vlogs, as this can impede the reflecting experience and frequency of vlogs and comments posted by the participants.